Introduction of “Honorable Mention“ Award at the International Olympiad in Informatics - Jovanov, Mile; Stankov, Emil (Vilnius University Press, 2020)
In 2020, there are 14 International Science Olympiads for secondary school students, which aim to gather teams from all the countries around the world, with the brightest young eligible students from each country. These Olympiads are not just a science competition but a means to care for talent in the particular scientific field. International Olympiad in Informatics (IOI) is one of the first five Olympiads that arose, after Mathematics, Physics and Chemistry, and before Biology Olympiad. Being the “summit” of the brightest students, they generously award recognitions to contestants in the form of gold, silver and bronze medals, and additionally – the so called “honorable mention” award. IOI is the only Olympiad that up until 2019 has not introduced the fourth-degree award – “honorable mention”. In this paper we explore the rules of the other four scientific Olympiads in order to compare their methods of awarding contestants to the current one used by IOI, and to use that analysis for proposing a rule change that will introduce “honorable mention” category at IOI. Furthermore, a set of possible approaches are considered, and for each one, the “retroactive” impact of the rule to the results of the last five IOI issues is presented. At the end, as a conclusion, the most appropriate approach is proposed.